The Nexus among Competition, Risk and Performance in Banking Sector of Saudi Arabia - Iftikhar, Nazish; Iqbal, Nadeem; Hanif, Hasan (Journal of Economic Impact, 2021)
The determination behind this research paper is to inspect the relation among competition, risk, and financial performance in the Saudi Arabian banking sector for 2011-2019. This paper used Two steps Generalized Method of Moment (GMM) as an estimation technique. This study focused on Lerner Index and Herfindahl-Hirschman Index to gauge bank competition and used three alternative measures for risk, namely credit risk, liquidity risk, and z-score. The coefficients of the Lerner Index and Herfindahl-Hirschman Index are significant and positive with profitability which signifies that higher competition in Saudi Arabian banks led to a decrease in profitability which is explained in the Structural Conduct Performance Hypothesis. Z-score shows a significant positive relationship with profitability. Credit risk has a positive relationship with profitability reveals that risk-adjusted returns are being targeted by risk-averse shareholders trying to gain more profits to compensate for the higher credit risk. The outcome of the study provides a comprehensive framework to the Central bank and other regulatory authorities to introduce micro and macro prudential policies that are aligned to the stability of the financial system.